Call for Prayer, Songs, Reports
Call for Prayer; report with a guest speaking about the brave Iraqi Army; report about activated civil defense force that is destroying enemy bombs; Saddam greets the brave Iraqi people; Saddam's letter to the people of Iraq, calling them brave and promising victory, read by Sahhaf; songs interspersed.